Soft tissue tumor imaging in adults: whole-body staging in sarcoma, non-malignant entities requiring special algorithms, pitfalls and special imaging aspects. Guidelines 2024 from the European Society of Musculoskeletal Radiology (ESSR) - Noebauer-Huhmann, Iris-Melanie; Vanhoenacker, Filip M; Vilanova, Joan C; Tagliafico, Alberto S; Weber, Marc-André; Lalam, Radhesh K; Grieser, Thomas; Vasilevska Nikodinovska, Violeta; de Rooy, Jacky W J; Papakonstantinou, Olympia; Mccarthy, Catherine; Sconfienza, Luca Maria; et al. (Springer Science and Business Media LLC, 2024)
The revised European Society of Musculoskeletal Radiology (ESSR) consensus guidelines on soft tissue tumor imaging represent an update of 2015 after technical advancements, further insights into specific entities, and revised World Health Organization (2020) and AJCC (2017) classifications. This second of three papers covers algorithms once histology is confirmed: (1) standardized whole-body staging, (2) special algorithms for non-malignant entities, and (3) multiplicity, genetic tumor syndromes, and pitfalls.
Keywords: Practice guideline; Consensus; Neoplasms; Connective and soft tissue; Diagnostic imaging